Expression, purification and reconstitution of the 4-hydroxybenzoate transporter PcaK from Acinetobacter sp. ADP1() - Pernstich, Christian (Academic Press, 2014)
The aromatic acid:H(+) symporter family of integral membrane proteins play an important role in the microbial metabolism of aromatic compounds. Here, we show that the 4-hydroxybenzoate transporter from Acinetobacter sp. ADP1, PcaK, can be successfully overexpressed in Escherichia coli and purified by affinity chromatography. Affinity-purified PcaK is a stable, monodisperse homotrimer in the detergent n-dodecyl-β-d-maltopyranoside supplemented with cholesteryl hemisuccinate. The purified protein has α-helical secondary structure and can be reconstituted to a functional state in synthetic proteoliposomes. Asymmetric substrate transport was observed when proteoliposomes were energized by applying an electrochemical proton gradient [Formula: see text] or a membrane potential (ΔΨ) but not by ΔpH alone. PcaK was selective in transporting 4-hydroxybenzoate and 3,4-dihydroxybenzoate over closely related compounds, confirming previous reports on substrate specificity. However, PcaK also showed an unexpected preference for transporting 2-hydroxybenzoates. These results provide the basis for further detailed studies of the structure and function of this family of transporters.